2023
DOI: 10.54112/bcsrj.v2023i1.297
|View full text |Cite
|
Sign up to set email alerts
|

Germplasm Potential for Different Advance Lines of Gossypium Hirsutum for Within Boll Yield Components

Abstract: Cotton production per hectare is low in Pakistan due to many biotic and abiotic factors.  As boll is the basic determinant for yield in cotton crop, a study on within boll yield parameters was carried out using 24 cotton bulk and 2 check varieties to check their variability for within boll yield components.  The experiment was performed in the research area of ​​the Department of Plant Breeding and Genetics, University of Agriculture, Faisalabad.  The genotypes were seeded in two replications following a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…However, variations in total chlorophyll contents and Monopodial Branches for cotton genotypes were significant, but the variations for Sugars contents were insignificant at 1% and 5%, respectively. Similar results were also found by Zafar et al (2022), Shafique et al (2023), Hussain et al (2023), and Yousaf et al (2023), who showed the presence of significant variations in cotton genotypes for morphophysiological and biochemical traits and emphasized on the utilization of diverse cotton germplasm to make proper selection.…”
Section: Analysis Of Variancesupporting
confidence: 82%
“…However, variations in total chlorophyll contents and Monopodial Branches for cotton genotypes were significant, but the variations for Sugars contents were insignificant at 1% and 5%, respectively. Similar results were also found by Zafar et al (2022), Shafique et al (2023), Hussain et al (2023), and Yousaf et al (2023), who showed the presence of significant variations in cotton genotypes for morphophysiological and biochemical traits and emphasized on the utilization of diverse cotton germplasm to make proper selection.…”
Section: Analysis Of Variancesupporting
confidence: 82%
“…of fertile tillers per plant, 1000 grain weight, and peduncle length affect wheat tolerance in soil (Ammar et al, 2022;Chaudhry et al, 2022). Drought stress is the major cause of abiotic factor for yield reduction (Imtiaz et al, 2022;SHAFIQUE et al, 2023). Drought stress affects crop plants which disturb the grain production from seedling to ripening .…”
Section: Introductionmentioning
confidence: 99%